Implementasi Tata Kelola yang Baik melalui Reformasi Birokrasi di Kementerian Lingkungan Hidup Kehutanan - Niadania Apriliani Apriliani (Penerbit Goodwood, 2021)
Purpose: This study aimed to explain corporate governance and its application in the Ministry of Environment Forestry, one of a kind which is through Bureaucratic Reforms. Research methodology: This research was a descriptive study with a qualitative approach. The research subject was the Ministry of Environment and Forestry. The source and type of data used in this study were secondary data, with the data collection technique was done using a literature study. Results: The results show that the Ministry of Environment Forestry as a public servant has implemented the main/basic principles of Good Corporate Governance, namely that Responsibility, Independence, Fairness, Accountability, and Transparency, which was adapted into 8 (eight) aspects of change which became a road map to create added value for stakeholders and ensure that tasks are carried out honestly, transparently and responsibly to create good governance (Good Corporate Governance-GCG). Limitations: The weakness of this research was that most of the data could not be obtained from primary sources but relied on secondary data or other people's information. Contribution: This is hoped that the results of this research can be a reference used in further research and are expected to provide an overview of how the implementation of Good Corporate Governance-GCG at Ministry Environment and Forestry.